Fertility Desires and Fertility Control: Young Women's Contraceptive decision-making in Khayelitsha, South Africa - Falakhe, Zipho (Department of Public Health and Family Medicine, 2022)
Early fertility remains a public health concern in South Africa, with teenage pregnancy rates remaining high, and more significantly among black adolescent girls of low socioeconomic status. This indicates the unmet need of contraception for adolescent girls. Contraceptive use and non-use by young women of low socioeconomic status is a complex issue that reveals a range of political and socio-economic injustices. Barriers to contraceptive access and use have been identified to include: health care access, interaction with healthcare providers, genders norms, knowledge gaps, reproductive choices, socio-cultural attitudes and policing, intimate partner relationship dynamics, parental judgement, and side effects. To address this public health concern there has been an increase in the provision of contraceptives through the introduction of long-acting reversible contraceptive (LARC) methods. However, young women's response to LARC methods has been characterized by low and declining uptake and early removals. A tension exists between the way public health practitioners imagine meeting the contraceptive needs of young women of low-socio economic status and what it is acceptable as contraception by young women. This mini-dissertation aims to examine young women's perceptions of long-term contraception and LARC methods; specifically, the implant and intrauterine device (IUD) contraceptive methods in how they reveal young women's fertility attitudes and how it shapes their contraceptive decision-making. This examination foregrounds the individual, interpersonal relationships and social contexts that shape sexual and reproductive choices of young women. The mini dissertation is structured in two parts: the research protocol (Part A) and a manuscript for a journal article prepared for publication (Part B). Part A explores the factors that influence young women's contraceptive decision-making at three different levels, namely: the individual level, interpersonal relationship level and social and structural context level. For the aim of further understanding young women's contraceptive decision-making, PART B focusses on examining the tensions in the acceptability and uptake of LARC methods and long-term contraception use to explain low and ineffective contraceptive use by young women, which often result in unwanted pregnancies. The findings from this mini dissertation can add to the existing literature that examines why current contraceptive provision has been inadequate in meeting the contraceptive needs of young women of low socioeconomic status and significantly curbing early fertility. Additionally, they can provide valuable information to public health practitioners on how particular factors influence the acceptability of contraceptive methods and as well as the root causes of behaviors that result in ineffective contraceptive use resulting in early fertility. Therefore, providing clear points for public health intervention.